2022
DOI: 10.1111/cns.13905
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic glioma‐derived extracellular vesicles harboring MicroRNA‐10b‐5p enhance M2 polarization of macrophages to promote the development of glioma

Abstract: Introduction:The delivery of biomolecules by tumor cell-secreted extracellular vesicles (EVs) is linked to the development of glioma. Here, the present study was implemented to explore the functional significance of hypoxic glioma cell-derived EVs carrying microRNA-10b-5 (miR-10b-5p) on glioma with the involvement of polarization of M2 macrophages. Methods: EVs were isolated from hypoxia-stimulated glioma cells, and their role in polarization of M2 macrophages was studied by co-culturing with macrophages. miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
(92 reference statements)
0
17
0
Order By: Relevance
“…Moreover, miR-10b-5p contributes to glioma progression by targeting HOXB3 and WWC3 (38,39). Furthermore, miR-10b-5p, which is delivered by hypoxic glioma-derived extracellular vesicles, can accelerate macrophage M2 polarization, resulting in the progression of glioma ( 40 ). These results suggested that miR-10b-5p can have both oncogenic and tumor-suppressive roles, depending on the organ and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-10b-5p contributes to glioma progression by targeting HOXB3 and WWC3 (38,39). Furthermore, miR-10b-5p, which is delivered by hypoxic glioma-derived extracellular vesicles, can accelerate macrophage M2 polarization, resulting in the progression of glioma ( 40 ). These results suggested that miR-10b-5p can have both oncogenic and tumor-suppressive roles, depending on the organ and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, macrophages are phagocytic, and it has been demonstrated that exogenous EVs injected directly into the blood are cleared within two minutes by patrolling monocytes [54]. Previous studies have demonstrated that depending on the origin of the EVs, it can result in their polarization into M1 macrophages ( e.g ., adipocyte-derived EVs from diabetic subjects [55]; hepatocyte-derived EVs from NAFLD patients [56]; EVs from M1 macrophages induced by interferon-γ (IFN-γ) and LPS [57] or M2 (Human umbilical cord mesenchymal stem cell derived-EVs [58]; hypoxic glioma cell-derived EVs [59]). Here, we demonstrated that under HG conditions, M1 macrophages released EVs that can further polarize M0 recipient macrophages into M2 anti-inflammatory macrophages ( i.e .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NEDD4L was demonstrated to degrade the catalytic subunit PI3KCA of PI3Ks via the ubiquitin‐proteasome pathway (Wang et al, 2016). Meanwhile, hypoxic gliomas reduce NEDD4L expression in macrophages by secreting MicroRNA‐10b‐5p vesicles to counteract the inhibitory effect of NEDD4L on the PI3K/AKT pathway and M2‐like polarization of TAMs (Li et al, 2022). Interestingly, M2‐like TAMs can also regulate NEDD4L in tumor cells through exosomes, further affecting autophagy and aerobic glycolysis in cancer cells via UPS and promoting tumor progression (Feng et al, 2021; Wang, Wang et al, 2021).…”
Section: Effect Of the Ups On Tamsmentioning
confidence: 99%